Jean-Michel Basquiat (1960-1988) - Tschinkel, Paul.; Schjeldahl, Peter; Deitch, Jeffrey; Fab 5 Freddy, 1959-; Nosei, Annina; Miller, Marc H.; Inner Tube Video (New York : Inner-Tube Video, 1989)
Covers brief but dazzling career of 1980's Artworld superstar Jean-Michel Basquiat. Includes interviews with Peter Schjeldahl, Jeffrey Deitch, Fab 5 Freddie Brathwaite and Annina Nosei. Interview of Basquiat by Marc Miller.
VHS format.
Narrated by Sarah Berry.
Keywords: Basquiat, Jean Michel, -- 1960-1988.; Painters -- Interviews